Synthesis and characterization of a novel highly phosphonated water‐insoluble polymer. Issue 3 (18th July 2019) - Alter, Christian; Neumann, Beate; Stammler, Hans‐Georg; Hoge, Berthold
ABSTRACT: A novel polymer, functionalized by tetrafluoroaryl phosphonic acid units, was prepared by free‐radical polymerization of the corresponding styrene monomer. The obtained polymer was analyzed by gel permeation chromatography, differential scanning calorimetry, and spectroscopy (NMR, IR). Ion exchange capacity of the water‐insoluble polymer was determined in methanol solution by titration with 0.1M NaOH. The proton conductivity of the polymer of 9.91 × 10 −7 S cm −1 as disclosed by electrochemical impedance spectroscopy renders this polymer a promising candidate for solid electrolyte applications or as a water‐insoluble dopant for proton exchange membrane applications. © 2019 Wiley Periodicals, Inc. J. Appl. Polym. Sci.2020, 137, 48235. Abstract :